Impact of Covid–19 and Foreign Direct Investment on Indonesia’s Economic Growth - Suparta, I Wayan; Wiryawan, Driya; Ciptawaty, Ukhti; Wahyudi, Heru (International Journal of Economics and Financial Issues, 2025)
This study seeks to investigate the effects of COVID-19, foreign direct investment, inflation and rents from natural resources on Indonesia’s economic growth from 1990 to 2021. The analysis method used in this research is ordinary least square (OLS). A time-series data from an Indonesian study between 1990 and 2021. The results of this study indicate that COVID-19 and inflation have a significant adverse effect on Indonesia’s economic growth. Foreign direct investment and natural resource rents have a considerable beneficial impact. The results of this study are expected to be one of the key references in developing policy; strengthening basic needs facilities, controlling inflation, making policies that stimulate FDI, and continuing natural resource management.